2016
DOI: 10.1128/cvi.00739-15
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Supplementation at the Time of Immunization with a Cold-Adapted Influenza Virus Vaccine Corrects Poor Mucosal Antibody Responses in Mice Deficient for Vitamins A and D

Abstract: V itamin A deficiencies (VAD) and vitamin D deficiencies (VDD) have long been considered maladies in the developing world, but recent research demonstrates that children and adults of developed countries also suffer from vitamin deficits (1-4). Individuals with low vitamin levels are particularly vulnerable to infections of the gastrointestinal and respiratory tracts (5-8), the latter of which are responsible for one-fifth of all deaths among children under the age of five (1, 9).Vitamin A is ingested in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 53 publications
2
47
0
1
Order By: Relevance
“…Consistent with this finding, we have observed that laboratory animals with both VAD and VDD had weaker immune responses toward respiratory virus antigens than animals with either VAD or VDD alone; supplementation with vitamins A and D corrected these responses (39). …”
Section: Discussionsupporting
confidence: 62%
“…Consistent with this finding, we have observed that laboratory animals with both VAD and VDD had weaker immune responses toward respiratory virus antigens than animals with either VAD or VDD alone; supplementation with vitamins A and D corrected these responses (39). …”
Section: Discussionsupporting
confidence: 62%
“…The situation may be worsening, as low income families gain better access to ‘fast’ foods rather than unprocessed and fortified foods. Our study in Memphis showed that low vitamin A levels associated with low serum IgA as well as poor influenza virus-specific neutralizing antibodies [6]. A placebo controlled, randomized, blinded, clinical study is now in progress to determine if vitamin supplements can be partnered with the administration of influenza virus vaccines to increase vaccine-induced immune responses in vitamin-deficient or vitamin-insufficient children in Memphis (Clinicaltrials.gov, CTG ID# NCT02649192, FLUVIT ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A deficiencies (VAD) and insufficiencies are present in both developed and developing countries [69] and have been associated with poor immune responses toward respiratory tract pathogens [10, 11], as well as an increased incidence of and morbidity from respiratory disease in school age children. Knowing that prevention of infection is critical in these highly susceptible populations, we employed a murine model of VAD to determine if PCV-13 was efficacious in the context of VAD.…”
Section: Introductionmentioning
confidence: 99%
“…A proprietary FDT formulation, Zydis ® for olanzapine, an antipsychotic drug, has been produced by Catalent Pharma Solutions using their patented freeze-drying technology [34], but none is still available for vaccines [17]. Besides, to overcome the vitamin-A deficiency it is recommended to give vitamin-A supplements during the vaccination process, though the actual dose needs to be determined in human studies [35].…”
Section: The Oral Routementioning
confidence: 99%